Do board characteristics contribute to corporate social responsibility? - Paiva, I. (Proceedings of the XVII Congresso Internacional de Contabilidade e Auditoria, 2019)
This paper examines the association between board characteristics and corporate social responsibility. Using a sample of sample of 102 firms belonging to the World Business Council for Sustainable Development in Portugal, we construct an index of CSR based on the content analysis of the companies’ sustainability reports and run several regressions of board characteristics and firm-specific controls. Our results demonstrate that firms with greater board size, gender diversity board and board experience are associated with higher levels of corporate social responsibility. Overall, our empirical findings suggest that a stronger board composition may promote more corporate social responsibility and ethical reputation in Portuguese firms.